FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016. - Wilda Yulika Maulitdia; Azwir Nasir; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This researchwas aimed to examine the factors that affect earnings management in manufacturing companies food and beverage sub-sector listed in Indonesia Stock Exchange 2013-2016. The technique of sampling using purposive sampling is the population used as sample in the study is the population that meets the criteria sample. From these criteria, we got sample of 9 food and beverage subsector companies in Indonesia Stock Exchange year 2013-2016. The analysis of this research using SPSS version 22.00. data analysis techniques to test hypotheses using multiple linear regression approach. The results of this research prove that the factors that affect earnings management (Deferred Tax Expenses, Current Tax Expenses, Profitability, and tax planning). Deferred Tax Expense has no significant effect to earnings management with value 0,839> 0,05, Current Tax Expense does not have significant effect to earnings management with value 0,993> 0,05, profitability has no effect to earnings management with value 0,379> 0,05, tax planning have significant effect to earnings management with value 0,002 <0,05. The result of determination coefficient of R2 found that 46,2% from independent variable in this research able to influence dependent variable, while the rest 53,8% influenced by other variable not examined in this research.Keywords : Earning Management, Deferred Tax Expense, Current Tax Expense, Profitability, and Tax Planning